Pengaruh Level Subtitusi Protein Sel Tunggal (Cj Prosin) Pada Pakan Komersial Terhadap Performan Ayam Broiler - Samadi Samadi; Mira Delima; Zuraida Hanum; Muhammad Akmal (Jurnal Agripet, 2012)
The effect of level substitution of single cell protein (CJ Prosin) by commercial feed on broiler performanceABSTRACT. A research to find out the effect of the substitution level of single cell protein in commercial feed on Broilers performance was conducted from June to December 2011. The purpose of this experiment is to find out alternative protein sources for animal feedstuff that can be used as protein substitution in animal feed on body weight, feed consumption and feed conversion efficiency. The experiment is considered as preliminary experiment to observe the response of single cell protein on broiler performance. This research was carried out at experimental farm, Animal Husbandry Department, Syiah Kuala University. Totally, 250 DOC of Cobb breed with the average body weight 36,782,32 gr. used in this experiment. Completely Randomized Design was applied in this experiment with 5 treatments; P0 (commercial feed), P1(commercial feed substituted with 6% SCP), P2 (commercial feed substituted with 12% SCP) dan P3 (commercial feed substituted with 18%CSP). Each treatment consist of 5 replications with total of 20 treatments units. Feed was formulated with isoprotein and isoenergy based on NRC requirement ( 23% protein ; 3200 kcal ME/kg at the age of 1-2 week and 20 % protein ; 3200 kcal ME/kg at the age of 4-7 week). Data was analyzed by using SPSS program SPSS (Window 2008). Differences between treatment were stated by Duncans multiple range test. The results of the experiment showed that commercial feed substituted with the level of SCP was not significantly difference (P0.05) on body weight gain, feed consumption, and feed conversion ratio. On the other hand, administration of SCP as substituted feed commercial on the level of 12 % and 16 % influenced significantly (P0.05) on body weight gain and feed conversion ratio, but not on feed consumption at the level of 12% SCP. As a conclusion, the use of SCP as animal feed sources in commercial feed only could be tolerated at the level of 6%.